Ierodiacon. Notă lexicografică - Ștefănescu, Maria; Minică, Mircea (Studia Romanica Posnaniensia, 2023)
In the present study, we aim to provide a critical analysis of the treatment of the word ierodiacon (hierodeacon) in several Romanian dictionaries. Following the investigation of a substantial number of documents, we also intend to show that there was a period in the history of the Romanian language in which a neutralization of the semantic opposition “married deacon (diacon de mir)” / ”monk deacon (diacon călugăr)” took place in some contexts, the term ierodiacon being used for both meanings. This phenomenon was not recorded in the historical dictionary of the Romanian language (relevant for the example under discussion being the old series, DA, coordinated by S. Pușcariu) nor in any other Romanian dictionary that we are aware of. At the end of the study we intend to add some theoretical reflections on the semantic evolution of ierodiacon, also referring to the way in which the entry for this term could be structured in the historical dictionary of the Romanian language.